2020
DOI: 10.1038/s41598-020-60671-6
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Lactobacilli-containing Vaginal Probiotic or Metronidazole Use to Prevent Bacterial Vaginosis Recurrence: A Pilot Study Incorporating Microscopy and Sequencing

Abstract: Bacterial vaginosis (BV) is associated with HIV acquisition and adverse pregnancy outcomes. Recurrence after metronidazole treatment is high. HIV-negative, non-pregnant Rwandan BV patients were randomized to four groups (n = 17/group) after seven-day oral metronidazole treatment: behavioral counseling only (control), or counseling plus intermittent use of oral metronidazole, Ecologic Femi+ vaginal capsule (containing multiple Lactobacillus and one Bifidobacterium species), or Gynophilus LP vaginal tablet (L. r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…The BactQuant 16S rRNA gene qPCR (Liu et al, 2012) was only done in the Rwanda VMB study (N = 379, of which 158 samples were not influenced by the interventions). The 16S rRNA gene concentration per sample was used to convert the relative abundances of that sample into estimated concentrations as previously described (van de Wijgert et al, 2020a). We used both relative abundances as well as estimated concentrations for the Rwanda VMB study, but only had relative abundances for the other two studies.…”
Section: Sequencing and Other Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BactQuant 16S rRNA gene qPCR (Liu et al, 2012) was only done in the Rwanda VMB study (N = 379, of which 158 samples were not influenced by the interventions). The 16S rRNA gene concentration per sample was used to convert the relative abundances of that sample into estimated concentrations as previously described (van de Wijgert et al, 2020a). We used both relative abundances as well as estimated concentrations for the Rwanda VMB study, but only had relative abundances for the other two studies.…”
Section: Sequencing and Other Laboratory Methodsmentioning
confidence: 99%
“…The Rwanda VMB study screened HIV-negative, nonpregnant, pre-menopausal women at high risk of sexually transmitted infections (STIs) for BV (van de Wijgert et al, 2020a). Women with BV were treated with metronidazole for seven days, and when cured of BV and other urogenital infections, were randomized to no intervention, or intermittent use of oral metronidazole or two different lactobacilli-containing vaginal probiotics for 2 months.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…In addition, L. rhamnosus BMX 54 also showed its potential to be used as adjuvant treatment in reshaping vaginal microbiota and by reducing BV recurrence after six to nine months of treatment [ 171 ]. Recent evidence showed that intermittent application of vaginal capsule (containing Lactobacillus acidophilus W70, Lactobacillus brevis W63, Lactobacillus helveticus W74, Lactobacillus plantarum W21, Lactobacillus salivarius W24, and Bifidobacterium bifidum W28) restored Lactobacillus -dominated vaginal microbiota and significantly reduced risk of BV incidence by 2.8-fold as compared to non-treated control group (10.18 per person-year) [ 172 ]. Meanwhile, the usage of lactobacilli could also reduce the rate of VVC recurrence.…”
Section: Potential Of Lactobacillus In Keeping Vagmentioning
confidence: 99%
“…Product efficacies were not known during the trial, and the efficacy results of the pilot trial are reported elsewhere. 17 Briefly, the vaginal probiotics did improve the vaginal environment (increased lactobacilli and reduced BV-associated bacteria) compared with counselling only, but not as much as oral metronidazole did.…”
Section: Methodsmentioning
confidence: 94%
“…Other clinical exclusion criteria were applied but were rare. 17 Women were recruited by study staff with the assistance of Community Mobilisers who had strong ties with local high-risk women (particularly sex workers). study products and dosing Ecologic Femi+ (EF+; Winclove Probiotics, Amsterdam, Netherlands) is a vaginal capsule containing lyophilised lactic acid-producing bacteria.…”
Section: Study Populationmentioning
confidence: 99%